2019
DOI: 10.1186/s12944-019-1149-6
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxysteroid sulfotransferase 2B1 affects gastric epithelial function and carcinogenesis induced by a carcinogenic agent

Abstract: BackgroundA healthy gastric mucosal epithelium exhibits tumor-suppressive properties. Gastric epithelial cell dysfunction contributes to gastric cancer development. Oxysterols provided from food or cholesterol oxidation in the gastric epithelium may be further sulfated by hydroxysteroid sulfotransferase 2B1 (SULT2B1), which is highly abundant in the gastric epithelium. However, the effects of SULT2B1 on gastric epithelial function and gastric carcinogenesis are unclear.MethodsA mouse gastric tumor model was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…In addition, hydroxysteroid sulfotransferase decreases the levels of cholesterol and oxysterols including 27HC [ 95 , 96 ]. Although the expression and function of this enzyme are related to some cancers including skin, liver, and gastric cancers [ 96 , 97 ], the enzyme is not specific to 27HC and its physiological function is not yet clear. In regard to pharmacological interventions of 27HC levels, statins, cholesterol-lowering drugs, and some CYP enzyme inhibitors reduce the 27HC levels as well, but they are not specific to 27HC, so it is hard to examine the direct impact of decreased 27HC on the disease [ 72 ].…”
Section: Enzymes and Drugs That Lower 27hc Levelsmentioning
confidence: 99%
“…In addition, hydroxysteroid sulfotransferase decreases the levels of cholesterol and oxysterols including 27HC [ 95 , 96 ]. Although the expression and function of this enzyme are related to some cancers including skin, liver, and gastric cancers [ 96 , 97 ], the enzyme is not specific to 27HC and its physiological function is not yet clear. In regard to pharmacological interventions of 27HC levels, statins, cholesterol-lowering drugs, and some CYP enzyme inhibitors reduce the 27HC levels as well, but they are not specific to 27HC, so it is hard to examine the direct impact of decreased 27HC on the disease [ 72 ].…”
Section: Enzymes and Drugs That Lower 27hc Levelsmentioning
confidence: 99%
“…Cholesterol sulfate (CS) is a sulfated derivative of cholesterol catalyzed by hydroxysteroid sulfotransferase 2B1 (SULT2B1) 12 , 13 . Our previous study, in addition to others, found that SULT2B1 promoted liver regeneration in a partial hepatectomy (PH) model, increased hepatic oval cell proliferation in a chemical-induced liver injury model, and accelerated the growth of multiple cells 14 17 . CS is critical in several biological processes, including epidermal differentiation, sperm capacitation, platelet adhesion, blood clotting, fibrinolysis, gluconeogenesis, T cell receptor signaling, and cell invasion 18 22 .…”
Section: Introductionmentioning
confidence: 70%
“…Hong et al. [47] showed that SULT2B1 affects gastric epithelial function and carcinogenesis induced by a carcinogenic agent. Hu et al.…”
Section: Discussionmentioning
confidence: 99%